Imaging markers of brain network disruption in multiple sclerosis - Welton, Thomas (2017)
Cognitive impairment and fatigue are prevalent and impactful symptoms of multiple sclerosis (MS). Effective markers are required by clinical studies to accurately test the efficacy of treatments for these symptoms. Graph analysis of brain networks based on magnetic resonance imaging (MRI) data can feasibly provide useful candidate markers of cognitive impairment and fatigability in MS which may be more objective, reliable and specific than existing markers. My original contribution to knowledge is therefore an exposition of the following hypothesis: “summary graph-theoretic descriptors of brain network organisation are good candidate markers of cognition or fatigue in MS”. To achieve this, network metrics were assessed based on three main criteria: reliability (“are the measurements the same across time and settings?”), validity (“do they measure what they are supposed to measure?”) and responsiveness (“are they altered when a change in cognitive state is induced?”).